STRUKTUR TUTURAN BAHASA INGGRIS DALAM WISATA KULINER MAKANAN LOKAL BALI PADA KANAL YOUTUBE - I Gusti Ayu Agung Dian Susanthi; Anak Agung Istri Manik Warmadewi; Dewa Ayu Kadek Claria; I Gusti Ngurah Adi Rajistha; Kuntayuni (Universitas Warmadewa, 2023)
Nowadays, human life is very close to technology. Community activities can be uploaded through their personal accounts on social media such as Facebook, Instagram or YouTube channels. The number of followers or followers of the account can number in the thousands, even hundreds of thousands, the account can also be used as a model to become popular or promote. The term for those who get money from social networks, especially YouTube, is YouTuber. Youtuber activity is something interesting to study, one of which is when the YouTuber is on a culinary tour or is enjoying the specialties of the local community, they use English as the language of instruction in carrying out their tourism activities that they upload. How the structure of the conversation they use is one of the interesting things to study. Given the existence of videos when presenting or explaining traditional food, it can also be used as a reference by students or other waiters. Thus, it is necessary to study the form of conversation patterns used by YouTubers in their uploaded videos. This research is qualitative research. The source of the research data is uploaded videos from YouTubers, especially culinary activities, the process of which is then transcribed to determine the structure of conversations by YouTubers on the YouTube channel. Keywords: Balinese menu; conversation structure; culinary tourism; Youtube